Impacto da institucionalização na capacidade cognitiva de idosos - Prado, Maiby Cristine [UNESP]; Pinelli, Lígia Antunes Pereira [UNESP]; Montandon, Andréia Affonso Barretto [UNESP]; Fais, Laiza Maria Grassi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Cognitive ability is one of the first tests to be applied in the elderly when they start a dental treatment, because it is fundamental to understanding the instructions that are passed during treatment. It is known that the education of an individual is a factor that interferes with this ability, however, the institutionalization of the elderly is still poorly understood. Thus, the aim of this study was to compare the cognitive abilities of elderly residents in a Long Term Care Institution and non-residents. It was used the Mini Mental State Examination test (MMSE) in 67 elderly residents,39 residents of San Francisco de Assis (group I) and other 28 non-residents in Long-Term Care Institution (group NI). The average age for all seniors was approximately 76 years. It was identified a statistically significant difference between the groups in terms of education (p = 0.05). The total average of the MMSE score for the group I was 17.67 ± 6.31 and for the NI group was 20.71 ± 3.35, with statistically significant diference between groups (p = 0.01). The comparison between age vs. MMSE showed inverse correlation only for group I (p = 0.028). It is concluded that the institutionalization can negatively influence the cognitive capacity of the elderly.

A capacidade cognitiva é um dos primeiros testes que devem ser aplicados em idosos quando iniciam um tratamento odontológico, isso porque é de fundamental importância a compreensão das instruções que são passadas durante o tratamento. Sabe-se que a escolaridade de um indivíduo é um fator que interfere nesta capacidade, entretanto, a institucionalização do idoso ainda é pouco compreendida. Sendo assim, o objetivo deste estudo foi comparar a capacidade cognitiva de idosos residentes em uma Instituição de Longa Permanência e não residentes. Foi aplicado o teste Mini Exame do Estado Mental (MEEM) em 67 idosos, 39 residentes no Lar São Francisco de Assis (grupo I) e outros 28 não residentes em Instituição de Longa Permanência (grupo NI). A idade média para todos os idosos foi de aproximadamente 76 anos. Não foi identificada diferença estatíticamente significante entre os grupos com relação à escolaridade (p=0,05). O escore médio total do MEEM para o grupo I foi de 17,67 ± 6,31 e para o grupo NI foi de 20,71 ± 3,35, com difernça estatisticamente significante entre os grupos (p=0,01). A comparação idade vs MEEM mostrou correlação inversamente proporcional apenas para o grupo I (p=0,028). Conclui-se que a institucionalização pode influenciar de forma negativa a capacidade cognitiva dos idosos.
Keywords: Aged; Cognition; Homes for the aged; Idoso; Cognição; Instituição de longa permanência para idosos